2012
DOI: 10.1097/mrr.0b013e3283527d29
|View full text |Cite
|
Sign up to set email alerts
|

Modified graded motor imagery for complex regional pain syndrome type 1 of the upper extremity in the acute phase

Abstract: Complex regional pain syndrome (CRPS) is a pathologic condition in which the painful experience is disproportionate in time and intensity in comparison with the inciting event. At present, the pathophysiology of CRPS is not well understood. Several studies have indicated that cortical reorganization plays a role in the persistence of the symptoms. A new promising approach, graded motor imagery (GMI), seems to be effective, but there are limited data for the CRPS-1 upper extremity population. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
2
32
0
2
Order By: Relevance
“…Although the GMI intervention reported by Mosely had significant functional, pain-reducing, and edema-reducing benefits, it may have limited feasibility as it requires performing a home program for 10 min each waking hour. For this reason, Lagueux et al [ 53 ] designed and implemented a modified approach to GMI with three 10 min sessions performed daily. In a six-week program, persons with acute type 1 CRPS reported significantly less pain ( p = 0.046) on McGill Pain Questionnaire, and improved maximum grip strength measured by dynamometry ( p = 0.040).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the GMI intervention reported by Mosely had significant functional, pain-reducing, and edema-reducing benefits, it may have limited feasibility as it requires performing a home program for 10 min each waking hour. For this reason, Lagueux et al [ 53 ] designed and implemented a modified approach to GMI with three 10 min sessions performed daily. In a six-week program, persons with acute type 1 CRPS reported significantly less pain ( p = 0.046) on McGill Pain Questionnaire, and improved maximum grip strength measured by dynamometry ( p = 0.040).…”
Section: Methodsmentioning
confidence: 99%
“…In a six-week program, persons with acute type 1 CRPS reported significantly less pain ( p = 0.046) on McGill Pain Questionnaire, and improved maximum grip strength measured by dynamometry ( p = 0.040). The present protocol is based on the modified GMI (mGMI) approach by Lagueax et al [ 53 ] which involved four stages of: 1) Laterality, 2) Explicit motor imagery, 3) Mirror therapy with unaffected hand only and 4) Mirror therapy with bilateral hands. The present study will only involve use the first three phases, given the constraint of cast immobilization.…”
Section: Methodsmentioning
confidence: 99%
“…The MI technique has had a significant effect of reducing pain in CRPS-1 after hand fracture, 26 , 29-32 decreasing the intensity of pain and promoting increased functionality, 21 , 26 ,31,32,47, 48 that can be maintained even after 6 months of intervention (see Table 1 ). 32 However, some individuals, who have suffered spinal cord injury, 49 or chronic CRPS in the arm, 29 cannot benefit from the use of MI because there are still flaws in their use.…”
Section: Methodsmentioning
confidence: 99%
“…The participants performed the GMI therapy at home, 10 minutes per session, 3 times per day, 6 times a week, for 6 weeks. 23 The description and settings of the GMI process are detailed in appendix (see Appendix A, Supplemental Digital Content 1, http://links.lww.com/CJP/A446 ). Before the beginning of each phase, the clinician carefully explained the GMI program to the participant.…”
Section: Graded Motor Imagery (Gmi) Interventionmentioning
confidence: 99%
“…14,16,17 But many audited patients in these previous studies reported that complying with exercises every waking hour was not feasible for them (75% compliance rate was reported). Our methodological choice regarding the frequency of the exercises was based on previous positive findings 23 and the fact that this exercise regimen was more respectful of their daily routine and quality of life during the intervention. 29,54 This methodological choice also probably contributed to the perfect compliance we observed for our two groups.…”
Section: Lack Of Treatment Effect In the Placebo Groupmentioning
confidence: 99%